1997
DOI: 10.3109/00207459709000630
|View full text |Cite
|
Sign up to set email alerts
|

Middle Latency Auditory Evoked Potentials in Congenitally Blind and Normal Sighted Subjects

Abstract: Middle latency auditory evoked potentials were recorded in two groups of ten subjects each, viz, congenitally blind (CB) and age-matched subjects with normal vision (NV). The age range for both groups was 13 to 16 years. The CB group subjects had peripheral deficits, with absence of visual evoked responses. The peak latency of the Nb wave (the maximum negativity between 38 and 48 ms) was significantly lower in the CB group compared to NV group (p < .05, one-tailed, two factor ANOVA, Tukey test). In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
1
2
1
1
Order By: Relevance
“…These authors argued that the decreased signal could be reflecting a greater processing efficiency. As they also remark, this hypothesis is supported by previous electrophysiological studies showing shorter latencies of early evoked potentials originated in the auditory cortex in early-blind individuals (Röder et al, 1996;Naveen et al, 1997Naveen et al, , 1998Manjunath et al, 1998), as well as the reduced metabolic responsiveness in a PET study of auditory localization with monkeys (Recanzone et al, 1993).…”
Section: Plasticity and Efficiency In Music Learningsupporting
confidence: 68%
“…These authors argued that the decreased signal could be reflecting a greater processing efficiency. As they also remark, this hypothesis is supported by previous electrophysiological studies showing shorter latencies of early evoked potentials originated in the auditory cortex in early-blind individuals (Röder et al, 1996;Naveen et al, 1997Naveen et al, , 1998Manjunath et al, 1998), as well as the reduced metabolic responsiveness in a PET study of auditory localization with monkeys (Recanzone et al, 1993).…”
Section: Plasticity and Efficiency In Music Learningsupporting
confidence: 68%
“…11 This finding is in agreement with previous studies, where they found that the peak latencies of both the Pa and Nb waves was significantly shorter in the congenitally blind compared to the normal sighted subjects. 12,13 The mean pattern of amplitude of MLAEPs (Na, Pa, Nb) did not show any significant difference between the two groups, except for Nb wave where it showed some significance which is in contrast to the study which showed that the peak amplitude of the Pa wave recorded from the occipital area of the congenitally blind individuals was significantly less than that of the normal sighted subjects, recorded from the same site. 12 It appears that in the blind subjects' changes in the generators of the middle latency auditory evoked potentials are mainly related to latency rather than to the scalp distribution of these components.…”
Section: Resultscontrasting
confidence: 74%
“…One hypothesis is that the decreased volume and intensity of signal detected in the EB group likely reflects greater processing efficiency within the first stages of auditory cortical analysis relative to late blind and sighted counterparts. This hypothesis is supported by electrophysiological studies revealing shorter latencies of early-evoked potentials (such as the Pa, Nb and N100) originating from electrodes placed over core and belt areas of auditory cortex in the EB [31, 18, 19, 20] and reduced metabolic responsiveness in a PET study of auditory localization [30]. Increased efficiency within temporal cortex during auditory perception appears to be a function of ‘loss-of-sight’ occurring before the closure of critical periods within development rather than a non-specific use-dependent mechanism.…”
mentioning
confidence: 80%
“…To date, no fMRI study has specifically focused on signal alterations within auditory cortex of he blind. A few event related potential (ERP) studies have examined the effects of blindness on auditory areas demonstrating electrophysiological changes around the core and belt regions of auditory cortex [8, 18, 19, 20]. For instance, one magnetoencephalography (MEG) study reported an expansion of tonotopic fields around the primary auditory cortex in response to low and high frequency bursts in a combined sample of individuals with acquired or late-onset blindness (LB) and EB peers [8].…”
mentioning
confidence: 99%